Electromagnetic radiation reduction using novel metamaterial for cellular applications - Tamim, A. M.; Faruque, M. R. I.; Khandaker, Mayeen Uddin *; Islam, M. T.; Bradley, D.A. * (Elsevier, 2021)
Excessive exposure to radiation has an adverse impact on human health, as an increase in body temperature may damage human organs or tissues, including the brain, eyes, and skin. Hence, this study assessed the effect of overexposure of radiation on the human head by analysing specific absorption rate (SAR) and reduction of SAR through the use of novel metamaterial (MTM). The SAR reduction was performed for GSM 900 MHz and 1800 MHz bands. A high-frequency electromagnetic simulator was employed throughout this study. The SAR investigation was performed on the head model for three categories of usage, namely voice calling, messaging, and video calling. This study looked into the impact on SAR of various free space distances between mobile phone and head model. A novel electric field driven LC (ELC) resonator-based MTM was used to reduce SAR. Based on the properties of the tissue, the rate of tissue absorption escalated with an increase in radiated power, especially when the distance between head and mobile phone decreased. The study outcomes signified that MTM could decrease a significant amount of SAR. This is beneficial to protect the human body from harmful radiation, wherein the distance from the device in biological effect should be maintained.